The Limited Impact of Exposure Duration on Holistic Word Processing - Chen, Changming; Abbasi, Najam ul Hasan; Song, Shuang; Chen, Jie; Li, Hong (Frontiers in Psychology, 2016)
The current study explored the impact of stimuli exposure duration on holistic word processing measured by the complete composite paradigm (CPc paradigm). The participants were asked to match the cued target parts of two characters which were presented for either a long (600 ms) or a short duration (170 ms). They were also tested by two popular versions of the CPc paradigm: the “early-fixed” task where the attention cue was visible from the beginning of each trial at a fixed position, and the “delayed-random” task where the cue showed up after the study character at random locations. The holistic word effect, as indexed by the alignment×congruency interaction, was identified in both tasks and was unaffected by the stimuli duration in both tasks. Meanwhile, the “delayed-random” task did not bring about larger holistic word effect than the “early-fixed” task. These results suggest the exposure duration (from around 150 ms to 600 ms) has a limited impact on the holistic word effect, and have methodological implications for experiment designs in this field.